HUBUNGAN TINGKAT PENGETAHUAN TENTANG KEPUTIHAN DENGAN PERILAKU PENCEGAHAN KEPUTIHAN PADA REMAJA PUTRI DI SMA DHARMA PRAJA DENPASAR: THE CORRELATION BETWEEN LEVEL OF KNOWLEDGE ABOUT LEUCORRHOEA AND PREVENTION OF LEUCORRHOEA BEHAVIOR ON TEENAGE GIRLS AT SMA DHARMA PRAJA DENPASAR - Citrawati, Ni Ketut; Nay, Herminia Carolina; Lestari, R. Tri Rahyuning (Stikes Wira Medika Bali, 2019)
Leucorrhoea is a symptom in the form of a liquid that is not in the form of blood coming out of genetal organs. In Indonesia, about 90% of women have the potential to experience leucorrhoea because the country of Indonesia is a tropical climate, so young fungi develop which result in many cases of leucorrhoea. Leucorrhoea in teenagers can be caused by bad behavior of leucorrhoea precaution. Knowledge is a factor to build behavior in teenager. This study aims to analyze the correlation between level knowledge about leucorrhoea with prevention behavior leucorrhoea for teenage girls at SMA Dharma Praja Denpasar. The type of research is quantitative by using descriptive correlation design method with cross sectional approach. The population in this study were female students of class X at SMA Dharma Praja Denpasar as many 124 people. The technique sampling is using simple random sampling with total sample of 95 respondents. Statistical tests using the Spearman Rank correlation test. The results showed that more teenager with good knowledge of leucorrhoea have good behavior in leucorrhoea precaution (82.3%). The results of the statistical tests show that there is a significant correlation with the strong strength between knowledge about Leucorrhoea with prevention behavior leucorrhoea for teenage girls at Sma Dharma Praja Denpasar, with a significance value of 0,000 with a correlation coefficient of 0.722. The higher adolescent's knowledge, it will better for behavior of adolescents towards prevention of leucorrhoea. Based on this study, it is recommended that health workers be expected to work together with schools in providing information to students about reproductive health, especially leucorrhoea.